Laryngectomy and smoking: An analysis of postoperative risk. (3rd July 2017) - Brady, Jacob S.; Crippen, Meghan M.; Filimonov, Andrey; Eloy, Jean Anderson; Baredes, Soly; Park, Richard Chan Woo
Abstract : Objectives: To investigate the impact of smoking on complication rates following total laryngectomy. Study Design and Methods: The National Surgical Quality Improvement Program database was queried for all total laryngectomies between 2005 and 2014. Patients were identified as smokers (n = 561) or nonsmokers (n = 513) and compared via univariate and multivariate analyses. A nearest‐neighbor propensity score‐generating algorithm was used to build a subpopulation (n = 714) of matched cases and evaluated in a similar manner. Additionally, pack‐year data was available for select cases and analyzed appropriately. Results: On multivariate analysis of the unmatched cohort accounting for demographics and confounders, no significant difference in overall medical complications was identified between groups (odds ratio = 0.799, P = 0.495). Propensity matching corrected for all significantly distributed comorbidities, except for alcohol, which remained associated with the smoking group ( P = < 0.001). In the matched population, there were no significant differences in complication rates between the two groups. Pack‐year data was available for 340 patients. These cases were subdivided into cohorts with < 50 (n = 204) and 51+ (n = 136) pack‐years. Postoperative pneumonia, ventilation for more than 48 hours, sepsis, and overall medical complications were associated with > 50 pack‐years of smoking. After multivariate regression, sepsis and overall medical complications remained significant for the 51+ pack‐year smoking cohort. Conclusion: After accounting for confounding comorbidities, smoking is found to play an insignificant role in the development of postoperative complications following total laryngectomy. However, those with 51+ pack‐years are at an increased risk for postoperative sepsis and overall medical complications following these complex procedures. Level of Evidence: 4. Laryngoscope, 127:2302–2309, 2017